Assessment of Cardiotoxicity Incidence in Patients Receiving HER-2-Targeted Therapies for Breast Cancer in Saudi Arabia - Alaa Shahbar; Abdullah A Alhifany; Yasser M Alatawi; Mohammed Alnuhait; Abdullah Alshammari; Majed Alshamrani; Abdulhalim Kinsara; Atif AlQubbany; Mahasen Alharbi; Abdelmajid Alnatsheh; Meteb Alfoheidi (Clinical Medicine Insights: Oncology)
Background: HER2-targeting therapies may increase the risk of decreased left ventricular ejection fraction (LVEF), potentially leading to heart failure. The growing number of breast cancer survivors due to HER2-targeted treatments necessitates long-term cardiotoxicity management. Method: This retrospective study included HER2-positive breast cancer patients aged 18 or older who received at least 1 dose of HER2-targeting treatment between 2016 and 2020. The primary endpoint was the incidence of cardiotoxicity, defined as LVEF <50% with a 10% decline, LVEF drop by >15%, or onset of symptomatic heart failure. Secondary endpoints included the proportion of patients with baseline LVEF 50% to 55% developing cardiotoxicity, those discontinuing HER2 therapy due to heart failure, those treated with heart failure medications, and those continuing HER2 therapy while on heart failure medications. Another secondary outcome was the development of a hospital protocol for monitoring cardiotoxicity in these patients. Results: A total of 212 patients were included, with a median age of 56.5 years (interquartile range: 43-58 years). Twenty-two patients (10.37%) experienced cardiotoxicity from HER2-targeted treatment. Thirteen patients (6.13%) had asymptomatic heart failure with LVEF decrease of more than 10% to less than 50%. Five patients (2.35%) with LVEF less than 40% had asymptomatic heart failure, while 4 patients (1.88%) had symptomatic heart failure regardless of LVEF decline. HER2-targeted treatment was temporarily discontinued in 3 (13.63%) patients and permanently in 4 (18.18%) patients due to cardiotoxicity. The remaining 15 patients resumed treatment without interruption. Only 13 out of 22 patients were referred to cardiologists and prescribed heart failure medications. Conclusion: Close monitoring of LVEF in patients receiving HER2-targeting therapy can help health care providers initiate anti-heart failure medications to prevent LVEF deterioration and maintain HER2-targeting therapy.